Knowledge Mapping within an Organization - Nožička, Josef; Jirků, Petr, 1942-2017; Říhová, Zora, 1948-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2012)
Search for the knowledge within big companies could become pain not only for knowledge seekers, but as well for knowledge managers in case they want a solution, that reflects well actual state of knowledge of a company, allows discovering emerging areas of knowledge and at the same time its maintenance does not require huge amounts of effort. This doctoral thesis starts by a comprehensive analysis of needs of expertise location of current company, description of theoretical backgrounds, related approaches and fundamental directions in expertise location, analyses their advantages and disadvantages and on the ground of this analysis presents a new expertise location technique that tries to avoid disadvantages of current expertise location systems by keeping their advantages. The technique is designed to respect the needs of effective knowledge management within a company, which main assets are their employees, their knowledge reflected in unstructured documents they produce as a part of their daily work. Described knowledge mapping technique analyses document publication history of company members and proposes various measures to asses and characterize their knowledge. The implementation of the knowledge mapping technique allows its direct usage (as an expert search engine) as well as its own evaluation (validity of search engine results). The efficiency of proposed measures on various types of document sources (project directories/versioning repositories/etc.) and within various dimension configurations (current/overall knowledge search) is evaluated by the practical evaluation method introduced within the thesis. The evaluation took place in the environment of a middle-sized software company allowing seeing directly a practical usability of the expertise location technique.
The results of the evaluation are presented not only in statistical form, but in a form of suggestions of how to implement the model on various document sources within the company. The results suggest that described knowledge mapping technique is a viable approach in expertise location.
Vedoucí práce: Petr Jirků
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: informatika [obor disert. práce]; disertace; dissertations